2010
DOI: 10.3109/09553001003674863
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib therapy reduces radiation-induced pulmonary mast cell influx and delays lung disease in the mouse

Abstract: We conclude that imatinib treatment reduces radiation-induced mast cell influx into the lungs and delays the alveolitis or fibrosis response of mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 41 publications
9
29
0
1
Order By: Relevance
“…Our survey on mitigation studies also shows that nearly all are confined to only one mouse strain. Only two reports have included strain comparison (among KK, AKR, and C3H mice) and show that the extension of MSTs upon treatment with imatinib mesylate 121 or the CXCR antagonist G3IP 122 can vary 2-to 3-fold among the different strains.…”
Section: Implications For Selecting the Best Models In The Pre-clinicmentioning
confidence: 99%
“…Our survey on mitigation studies also shows that nearly all are confined to only one mouse strain. Only two reports have included strain comparison (among KK, AKR, and C3H mice) and show that the extension of MSTs upon treatment with imatinib mesylate 121 or the CXCR antagonist G3IP 122 can vary 2-to 3-fold among the different strains.…”
Section: Implications For Selecting the Best Models In The Pre-clinicmentioning
confidence: 99%
“…Lung damage was induced by whole-thorax irradiation (18 Gy; dose rate 0.6 Gy/min) using a Gammacell 137 Cs unit as described previously (5,9,(19)(20)(21)(22). The rest of the body was shielded with 3 cm of lead to reduce the beam strength to 3% in this area.…”
Section: Radiation Treatmentmentioning
confidence: 99%
“…G31P treatment has also been shown to block acute neutrophil infiltration to the lungs of endotoxemic guinea pigs (16) and piglets (17) and to reduce bronchoalveolar lavage neutrophilia in mice exposed intranasally to benzo(a)-pyrene (18). To assess the effect of the antagonist on both alveolitis and fibrosis, we examined the responses of AKR/J and KK/HIJ mice, which develop these phenotypes, respectively, after whole-thorax irradiation (19).…”
Section: Introductionmentioning
confidence: 99%
“…At the age of 8-10 weeks, mice were exposed to a single dose of 18 Gy to the thorax using a Gamma Cell Cesium-137 source as previously described (22,26). Mice were weighed weekly beginning 8 weeks after irradiation.…”
Section: Thoracic Irradiation and Experimental Groupsmentioning
confidence: 99%
“…Mice were euthanized when they showed signs of distress (ruffled fur, accelerated breathing, hunched posture, weight loss .15% of body weight). For these studies, groups of C57BL/6J and Ja18 -/-mice were euthanized not only when they showed signs of distress but also at specific time points (16,20,26 and 35 weeks) postirradiation. Control mice were not irradiated and were euthanized at matching time points.…”
Section: Thoracic Irradiation and Experimental Groupsmentioning
confidence: 99%